Pengaruh Komite Audit Perempuan, Pengalaman Kerja dan Pendidikan Akuntansi & Keuangan Terhadap Nilai Perusahaan Manufaktur - Gisela Gisela; Fitria Husnatarina; Rini Oktavia; Rapel Rapel; Sri Yuni; Iwan Christian (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The Author, 2024. The Influence of Female Audit Committees, Audit Committee Work Experience, and Audit Committee Accounting & Finance Education on the Value of Manufacturing Companies (In Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2022). Thesis Department of Accounting, Faculty of Economics and Business, Palangka Raya University. Supervisor: Dr. Fitria Husnatarina, SE., M.Si., Ak., CA and Rini Oktavia, SE., M.Sc. This research aims to explain the influence of female audit committees, audit committee work experience, and audit committee accounting & finance education on company value. This research uses secondary data, the population used in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique in this research was using a purposive sampling method. There are 23 manufacturing companies that meet the sample criteria in this research, so the observation data amounts to 92. The data analysis method in this research uses SPSS statistical tools with multiple regression analysis equations. The research results show that: (1) The existence of a female audit committee has an influence on increasing company value significantly; (2) Audit Committee Work Experience has a positive and significant effect on Company Value; and (3) Audit Committee Accounting and Finance Education has a positive and statistically significant relationship to Company Value.